Effect of different interfacial surface treatments on the shear bond strength of veneering ceramic and zirconia core - Marwa K. Youssef; Sanaa H. Abdelkader; Yasser M. Aly (BMC, 2023)
Abstract Background Several interfacial surface treatments of zirconia surfaces have been proposed to improve adhesion to ceramic veneering. However, information regarding the durability and effect of such treatments on the bond strength following such treatments is lacking. Aim of the study This study aimed to evaluate the shear bond strength between veneering ceramic and zirconia core after different interfacial surface treatments. Materials and methods Fifty-two discs (8 mm in diameter and 3 mm in height) were fabricated from zirconia blanks using a microtome cutting machine. Zirconia discs were divided into four groups (n = 13). Group I was subjected to air-borne abrasion using (Al2O3), group II was coated by bioglass, group III was coated with ZirLiner, and group IV was subjected to wash firing (sprinkle technique). A cylinder (4 mm in diameter and 3 mm in height) of veneering ceramic was fired on top of the zirconia core. Shear bond strength (SBS) between zirconia core and veneering ceramic was evaluated by using a universal testing machine. The data was collected and statistically analysed using One-Way ANOVA followed by multiple pairwise comparisons using Bonferroni adjusted significance level. The failure modes were assessed using a stereomicroscope for each group. Results The highest mean bond strength was recorded in group III (17.98 ± 2.51 MPa), followed by group II (15.10 ± 4.53 MPa), then group I 14.65 ± 2.97 MPa. The lowest mean bond strength was recorded in group IV (13.28 ± 3.55 MPa). Conclusions Surface treatments had an effect on the zirconia-veneer shear bond strength. Liner coating revealed the highest shear bond strength values, significantly higher in comparison to wash firing (sprinkle technique) .